The Effect of Exercise-Based Game Intervention on Reducing Depression in the Older Adults - Riyadh Sofian; Tri Laksono; ⁠Rizky Wulandari (International Journal Of Health Science, 2025)
The older adults are a population vulnerable to mental health problems, particularly depression. Exercise-based game is a game-based training activity that involves body movement according to given instructions and is considered effective in improving emotional balance and reducing depressive symptoms in older adults. This study aimed to determine the effect of exercise-based game and education on reducing depression levels among the older adults at the Posyandu Lansia Bugar Mandiri Bangunrejo, Yogyakarta. This experimental study employed a quasi-experimental approach with a pre-test and post-test two group design. The sampling technique used total sampling with 30 participants divided equally into two groups of 15 each. The training program was conducted three times a week for four weeks. The research instrument used the Geriatric Depression Scale, and data were analyzed using paired sample t-test and independent sample t-test. The results showed that both exercise-based game and education significantly reduced depression in the older adults (p = 0.00; p < 0.05). However, there was no significant difference between the two groups (p = 0.096; p > 0.05). In conclusion, both exercise-based game and education are effective in reducing depression among the older adults, but neither showed a significantly greater effect than the other.